If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (3y + 7)(4y + 5) Reorder the terms: 0 = (7 + 3y)(4y + 5) Reorder the terms: 0 = (7 + 3y)(5 + 4y) Multiply (7 + 3y) * (5 + 4y) 0 = (7(5 + 4y) + 3y * (5 + 4y)) 0 = ((5 * 7 + 4y * 7) + 3y * (5 + 4y)) 0 = ((35 + 28y) + 3y * (5 + 4y)) 0 = (35 + 28y + (5 * 3y + 4y * 3y)) 0 = (35 + 28y + (15y + 12y2)) Combine like terms: 28y + 15y = 43y 0 = (35 + 43y + 12y2) Solving 0 = 35 + 43y + 12y2 Solving for variable 'y'. Combine like terms: 0 + -35 = -35 -35 + -43y + -12y2 = 35 + 43y + 12y2 + -35 + -43y + -12y2 Reorder the terms: -35 + -43y + -12y2 = 35 + -35 + 43y + -43y + 12y2 + -12y2 Combine like terms: 35 + -35 = 0 -35 + -43y + -12y2 = 0 + 43y + -43y + 12y2 + -12y2 -35 + -43y + -12y2 = 43y + -43y + 12y2 + -12y2 Combine like terms: 43y + -43y = 0 -35 + -43y + -12y2 = 0 + 12y2 + -12y2 -35 + -43y + -12y2 = 12y2 + -12y2 Combine like terms: 12y2 + -12y2 = 0 -35 + -43y + -12y2 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(35 + 43y + 12y2) = 0 Factor a trinomial. -1((7 + 3y)(5 + 4y)) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(7 + 3y)' equal to zero and attempt to solve: Simplifying 7 + 3y = 0 Solving 7 + 3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3y = 0 + -7 3y = 0 + -7 Combine like terms: 0 + -7 = -7 3y = -7 Divide each side by '3'. y = -2.333333333 Simplifying y = -2.333333333Subproblem 2
Set the factor '(5 + 4y)' equal to zero and attempt to solve: Simplifying 5 + 4y = 0 Solving 5 + 4y = 0 Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4y = 0 + -5 4y = 0 + -5 Combine like terms: 0 + -5 = -5 4y = -5 Divide each side by '4'. y = -1.25 Simplifying y = -1.25Solution
y = {-2.333333333, -1.25}
| 3/-2+2=5 | | -11(-6)= | | 0=x^2-8x-48 | | 2x(x)=200 | | -12(4)= | | .15-.01(x+1)=-.02(2-x) | | 29=-9+r | | 15(-5)= | | -3(x+4)+15=12 | | 5x-60= | | 3+5x=-3x-53 | | 20=-5/8x | | -16=t-3 | | -12x=96 | | 2+5x=-3x-53 | | 3x^2=3+2x | | 2x-13=3x+18 | | -27=-4c-7 | | 34x/4591 | | 4(z+2)=2n+40 | | 0.4x-2.6=0.6 | | 342+4902049= | | 5/3y+7/5y | | 10-6x-15=8x+27-6x | | 4x^2=3+4x | | -2(t-1)+6t=8t-6 | | x/-5-4=-7 | | 8a-10=150 | | 4(3x+1)-8=12x-4 | | 1.2=0.6 | | 6xy+9xy= | | 5x+5=5(x+9) |